2011
DOI: 10.1007/s00445-010-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Dike emplacement near Parícutin volcano, Mexico in 2006

Abstract: A major seismic swarm occurred near Parícutin volcano between the end of May and early July 2006. More than 700 earthquakes with magnitude (M L ) exceeding 2.4 were located. Parícutin, located in the Michoacán-Guanajuato volcanic field in western Mexico, is well known as the site of the 1943 eruption in which a new 400 m cinder cone was constructed in what had been farmland. The 2006 swarm exhibits all of the characteristics typically associated with swarms of volcanic origins. The earthquake rate showed the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 26 publications
0
27
0
4
Order By: Relevance
“…Examples include Soufrière Guadeloupe, 1975-1976(Hirn and Michel 1979Dorel and Feuillard 1980;Feuillard et al 1983;Beauducel and Besson 2008), Akutan, Alaska, 1996(Lu et al 2000Power et al 2008), Mount Baker, Washington, 1975(Crider et al 2011), Iliamna, Alaska, 1996(Roman et al 2004Roman and Power 2011), Iwate, Japan, 1998(Nishimura and Ueki 2011), Parícutin, Mexico, 2006(Gardine et al 2011), Fourpeaked, Alaska, 2006(Gardine et al 2010), Mount Spurr, Alaska, 2004(Power 2004, and others. A few cases are well-studied, but many are poorly documented in the literature and so details of such events are often unavailable for comparison during an unrest episode.…”
Section: Introductionmentioning
confidence: 97%
“…Examples include Soufrière Guadeloupe, 1975-1976(Hirn and Michel 1979Dorel and Feuillard 1980;Feuillard et al 1983;Beauducel and Besson 2008), Akutan, Alaska, 1996(Lu et al 2000Power et al 2008), Mount Baker, Washington, 1975(Crider et al 2011), Iliamna, Alaska, 1996(Roman et al 2004Roman and Power 2011), Iwate, Japan, 1998(Nishimura and Ueki 2011), Parícutin, Mexico, 2006(Gardine et al 2011), Fourpeaked, Alaska, 2006(Gardine et al 2010), Mount Spurr, Alaska, 2004(Power 2004, and others. A few cases are well-studied, but many are poorly documented in the literature and so details of such events are often unavailable for comparison during an unrest episode.…”
Section: Introductionmentioning
confidence: 97%
“…Passarelli et al (2015b) showed that 3D dike geometry can explain oblique normal faulting sometimes observed in the region crowning a dike from the top to the side. The orientations of the pressure (P-) or tension (T-) axes derived from focal mechanism inversion support a model resulting often sub-perpendicular to the intrusion plane (Ukawa and Tsukahara, 1996;Roman and Cashman, 2006;Gardine et al, 2011). Dike-induced earthquakes generally show non-negligible non-DC components (Julian, 1983;Dahm and Brandsdóttir, 1997;Minson et al, 2007;Ruppert et al, 2011;Belachew et al, 2013).…”
Section: Magmatic Hypothesismentioning
confidence: 99%
“…The dike volume increases following asymptotic exponential growth (Rivalta, 2010). The earthquakes induced around the dike tip migrate with a similar asymptotic exponential growth of the distance to the magma chamber at speeds of the order of a few kilometers to tens of kilometers per day (Ukawa and Tsukahara, 1996;Keir et al, 2009;Gardine et al, 2011;Grandin et al, 2011;Ruppert et al, 2011;Maccaferri et al, 2016). On a distancetime graph the migrating seismicity often comprises two curves marking the migrating front and the line where the seismicity switches off, sometimes called the back-front (Brandsdóttir and Einarsson, 1979;Belachew et al, 2011;Grandin et al, 2011).…”
Section: Magmatic Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Dikes may reach lengths of tens of km, delivering magma and feeding eruptions for significant distances also outside volcanoes. However, dikes may often become arrested and not generate any eruption (e.g., Gardine et al, 2011). Several recent studies highlight the extremely rapid transfer of magma, up to m/s, from the mantle or shallower levels, even for rhyolitic compositions and in apparently unfavorable tectonic conditions (Castro and Dingwell, 2009;Ruprecht and Plank, 2013).…”
Section: Challenge 2: Propagation and Arrest Of Magmamentioning
confidence: 99%